Roselle (Hibiscus sabdariffa) as a Sustainable Herbal Supplement for Enhancing the Performance of Freshwater Ornamental Fish - Muhammad Ijaz; Setyawan Heru Tandyo (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study is to examine the effect of roselle (Hibiscus sabdariffa) supplementation on the performance of ornamental fish, including growth rate, survival rate, feed intake, and body pigmentation, through a systematic review of national and international research findings. Methodology: This study employed a literature review method using Google Scholar, ScienceDirect, and ResearchGate databases. Data were analyzed descriptively using Microsoft Excel 2021. Reference validation was based on ISSN and DOI verification. Literature selection, classification, and data extraction were performed systematically following PRISMA guidelines to ensure research reliability. Main Findings: The main findings show that Roselle (Hibiscus sabdariffa) contains bioactive compounds such as anthocyanins, flavonoids, and vitamin C that enhance fish health and immunity. Supplementation improved survival rate and feed intake but did not significantly increase color performance, as anthocyanins are not dominant pigments for coloration compared to carotenoids like astaxanthin and zeaxanthin. Novelty/Originality of this study: This study provides new insight into the potential use of Roselle (Hibiscus sabdariffa) as a natural feed additive for ornamental fish. Unlike previous studies focused on food fish, it highlights Roselle’s bioactive compounds in enhancing immunity and feed intake, offering an eco-friendly alternative to synthetic additives in sustainable aquaculture practices.